2023
DOI: 10.1192/j.eurpsy.2023.15
|View full text |Cite
|
Sign up to set email alerts
|

Early identification of treatment non-response in first-episode psychosis

Abstract: Background Approximately one-third of patients with psychotic disorders does not respond to standard antipsychotic treatments. Consensus criteria for treatment resistance (TR) may aid the identification of non-response and subsequent tailoring of treatments. Since consensus criteria require stability of clinical status, they are challenging to apply in first-episode psychosis (FEP). This study aims to investigate (a) if an adaptation of consensus criteria can be used to identify FEP patients with early si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 68 publications
1
1
0
Order By: Relevance
“…Two clinical studies, which strictly limited prescribed medications, reported differing results from ours, finding that the early non-response subgroup had significantly higher disease severity at baseline (based on total PANSS scores rather than CGI-SI) in first-episode schizophrenia patients ( 9 , 16 ). However, two other studies reported findings highly consistent with ours; specifically, early non-responders exhibited more severe psychopathological symptoms, including higher PANSS total scores and its three subscale scores ( 17 , 18 ). The contradictory results may stem from strict restrictions on prescribed medications and enrollment criteria.…”
Section: Discussionsupporting
confidence: 90%
“…Two clinical studies, which strictly limited prescribed medications, reported differing results from ours, finding that the early non-response subgroup had significantly higher disease severity at baseline (based on total PANSS scores rather than CGI-SI) in first-episode schizophrenia patients ( 9 , 16 ). However, two other studies reported findings highly consistent with ours; specifically, early non-responders exhibited more severe psychopathological symptoms, including higher PANSS total scores and its three subscale scores ( 17 , 18 ). The contradictory results may stem from strict restrictions on prescribed medications and enrollment criteria.…”
Section: Discussionsupporting
confidence: 90%
“…Participants in this interview study were all part of the completed TOP 10-year (30) (Thematically Organized Psychosis, TOP-10) and TIPS 20-year (14) (The Treatment and Intervention in Psychosis, TIPS-20) follow-ups of two catchment area-based FEP studies in Oslo, Norway (see cited studies for further information). Both cohorts were recruited from the majority of in-and outpatient mental health services in the urban Oslo area, with the catchment area covering about 90% of the Oslo population.…”
Section: Context Of the Studymentioning
confidence: 99%